A regard to the gender relations at the Technological University of Pereira, 1661-2010 - Pabón Patiño, Morelia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This text is framed as a research project of the group “Education and Human Development” 1, with the objective of analyzing the way of how the social dimension of the gender in the field of the Technological University of Pereira. It was a fundamental way in the participation of gender positioning and the power relationships. The mobilization of women in the first decades of the twentieth century, by the right of access to higher education and the creation of the Technological University of Pereira in 1958 facilitated the women’s access from “Gran Caldas” region to the university. The pioneering experience began with the engineering field contrasting with trends observed in other universities in the country. Then with the opening of new academic programs with diversified areas of their professionalism, in the lapse of time since the seventies until turn of the century period. The feminization of enrolment and the areas of knowledge in which participates as a student, plays cultural patterns and traditional social in relation to the educational development of women. There were repeated models of teaching and management fields that concerning the dimension of gender equity among the university teachers. Based on the interdisciplinary experience on the construction of the female thinking that arrived in the seventies, it is performed an exploratory analysis onthe journey of this object of study in the academic context, and the relationship between the academic woven and the relationship between the academy and the women’s movement in the region.